THE EFFECTIVENESS OF PROBLEM BASED LEARNING MODEL AND LEARNING STYLE ON MATHEMATICAL CREATIVE THINKING ABILITY OF STUDENTS OF SMA NEGERI 1 SALAMAN MAGELANG - Toifur, Imam; Sugiman, Sugiman; Santoso, Agus (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
This study aims to examine the effectiveness of the PBL model and learning styles on students' mathematical creative thinking abilities. This study is a quasi-experimental study with a non-equivalent control group design. The population of the study was 143 students of grade XII of SMA Negeri 1 Salaman Magelang in the 2024/2025 academic year who took advanced mathematics electives. The research sample was 71 students with a purposive sampling technique. Data collection with pretest-posttest questions on mathematical creative thinking abilities. The research instrument was in the form of descriptive questions covering fluency, flexibility, originality, and elaboration. For data analysis, the normality test, homogeneity test, and hypothesis test uses two way anova were used. The findings of the research results are as follows: (1) There is a difference in the ability to think creatively mathematically between students who have followed the PBL model and the direct learning model as shown by the Sig. 0.002 < 0.05. (2) There is no difference in the ability to think creatively mathematically between students with different learning styles as shown by the Sig. 0.122 > 0.05. (3) There is no significant interaction effect between the learning model and students' learning styles on the ability to think creatively mathematically as shown by the Sig. 0.245 > 0.05. ABSTRAKPenelitian ini bertujuan untuk mengkaji efektivitas model PBL dan gaya belajar terhadap kemampuan berpikir kreatif matematis siswa. Penelitian ini merupakan penelitian eksperimen kuasi dengan desain eksperimen non-equivalent control group design. Populasi penelitian adalah siswa kelas XII SMA Negeri 1 Salaman Magelang tahun ajaran 2024/2025 yang mengambil mata pelajaran pilihan matematika tingkat lanjut yang berjumlah 143 siswa. Sampel penelitian berjumlah 71 siswa dengan teknik purposive sampling. Pengumpulan data dengan soal pretest-posttest kemampuan berpikir kreatif matematis. Instrumen penelitian berupa soal uraian yang mencakup kelancaran, keluwesan, keaslian serta kemampuan memperinci, memperkaya dan mengembangkan. Untuk analisis data yang digunakan adalah uji normalitas, uji homogenitas, dan uji hipotesis menggunakan anova dua arah. Temuan hasil penelitian sebagai berikut: (1) Terdapat perbedaan kemampuan berpikir kreatif matematis antara siswa yang telah mengikuti model PBL dan model pembelajaran langsung ditunjukkan dengan nilai Sig. 0.002 < 0.05. (2) Tidak terdapat perbedaan kemampuan berpikir kreatif matematis antara siswa dengan gaya belajar yang berbeda ditunjukkan dengan nilai Sig. 0.122 > 0.05. (3)  Tidak ada pengaruh interaksi yang signifikan antara model pembelajaran dan gaya belajar siswa terhadap kemampuan berpikir kreatif matematis ditunjukkan dengan nilai Sig. 0.245 > 0.05.